Pengaruh Business Risk, Investment Opportunity Set, dan Sustainability Report Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Intervening - Tiara Kusuma Wardani; Nera Marinda Machdar (Jurnal Kajian dan Penelitian Umum, 2023)
This research aims to analyzze the influence of business risk, investment opportunity set and sustainability reporting on company value with profitability as a moderator. The population in this research is all manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2015-2022. Sample selection method using purposive sampling method. This type of research is qualitative and the type of data used is secondary data. Research results show that Business Risk has a positive effect on company value; Investment Opportunity Set has a positive effect on company value; Sustainabilitu Reporting has a positive effect on company value ; Business Risk has a positive effect on profitability Investment Opportunity set has a positive effect on profitability; sustainability reporting has a positive effect on profitabilitu can mediate the influence of the Investment Opportunitu Set on the value of the company; Profitability can mediate the influence of sustainability reporting on company value.